The Importance Of Pros For English Learning In Elementary School - Puspitasari, Devita Indah; Azhar, Farid Syahrul; Khasanah, Intan Aminatul (Prosiding University Research Colloquium, 2021)
The purpose of this activity is to determine the effect of learning media or teaching aids in learning English in elementary schools. This study uses classroom action research, in this study we get data that many elementary school students still have difficulty in learning English. Can increase the focus of learning on students and make students more enthusiastic about learning. Through flash card learning media, it can improve skills in reading the alphabet and also vocabulary. According to the data we took form several references, one of wich was in MI-Ar Rohman Semarang successfully implemented English learning through flashcard learning media successfully and students could easily learn English. Learned and can increase students’ learning motivation.